The Role of Sustainability Accounting in ESG Reporting Transparency - Dela Wahyu Putri Awanda; Devina Shava Amalia; Cholis Hidayati (International Forum of Researchers and Lecturers, 2025)
This study aims to understand how sustainable accounting practices can improve the transparency of reports related to environmental, social, and governance (ESG) aspects. This study uses a literature review method by examining 20 relevant previous studies. The discussion results indicate that sustainability accounting helps companies record and report financial and non-financial information transparently, thereby strengthening stakeholder trust and supporting decision-making. Additionally, digital technology enhances the effectiveness of ESG reporting, making it more accessible and accurate. Sustainability accounting is proven to be important not only for transparency but also for long-term business sustainability.